A large landslide event in a post‐glacial landscape: rethinking glacial legacy. Issue 11 (28th January 2013) - Davies, Timothy R. H.; Warburton, Jeff; Dunning, Stuart A.; Bubeck, Alodie A. P.
ABSTRACT: Threlkeld Knotts ( c . 500 m above sea level) in the English Lake District has hitherto been considered to be a glacially‐modified intrusion of microgranite. However, its surface features are incompatible with glacial modification; neither can these nor the subsurface structures revealed by ground‐penetrating radar (GPR) be explained by post‐glacial subaerial processes acting on a glacially‐modified microgranite intrusion. Here we re‐interpret Threlkeld Knotts as a very large post‐glacial landslide involving the microgranite, with an estimated volume of about 4 × 10 7 m 3 . This interpretation is tested against published and recent information on the geology of the site, the glacial geomorphic history of the area and newly‐acquired GPR data. More than 60 large post‐Last Glacial Maximum (LGM) rock–slope failures have significantly modified the glaciated landscape of the Lake District; this is one of the largest. Recognition of this major landslide deposit in such a well‐studied environment highlights the need to continuously re‐examine landscapes in the light of increasing knowledge of geomorphic processes and with available technology in currently active or de‐glaciating environments. Copyright © 2012 John Wiley & Sons, Ltd.